Climate Change And Food Security In Nepal - Pant, Krishna Prasad (Journal of Agriculture and Environment, 2013)
Climate change is posing a threat on present and future food security in low income countries. But, the actual effect of the climate change on food security is not known. Using secondary data reported by the government, the paper examines the effects of climate change on food security in Nepal in the context of policies of commercialization of farm production. Statistical analysis is used to delineate the situation of food security in the country and regression analysis for exploring the effects of global warming on domestic production of major cereals. The results are discussed at global, national, household and individual levels empirically and qualitatively. The results suggest that a rise in minimum temperature decreases the productivity of rice increasing threat of food insecurity. The paper suggests some policy measures for improving food security situation in the country and open up some areas for further research. The Journal of Agriculture and Environment Vol:13, Jun.2012, Page 9-19 DOI: http://dx.doi.org/10.3126/aej.v13i0.7582